Fabrication of Er3+/Yb3+ Co-Doped Bi5O7I Microsphere With Upconversion Luminescence and Enhanced Photocatalytic Activity for Bisphenol A Degradation - Cao, Baowei; Gong, Siwen; Zubairu, Siyaka Mj; Liu, Lingna; Xu, Yunhua; Guo, Lei; Dang, Rui; Zhu, Gangqiang (Frontiers in Chemistry, 2020)
Uniform porous Er3+/Yb3+ co-doped Bi5O7I microspheres were synthesized by two-step chemical method and it possess excellent photocatalytic performance and up-conversion luminescence properties. The photocatalytic performances of the photocatalysts were studied by degradation of bisphenol A (BPA) in aqueous solution under visible light irradiation and different monochromatic light. The photocatalytic performance of Er3+/Yb3+ co-doped Bi5O7I sample is better than that of the pristine Bi5O7I sample, and Er3+-doped Bi5O7I samples. Moreover, Er3+/Yb3+ co-doped Bi5O7I possesses photocatalytic ability with a red light monochromatic LED lamp (3W, λ= 630 nm) and an infrared monochromatic LED lamp (100W, λ= 940 nm) irradiation whose wavelength are longer than the absorption limiting wavelength of pristine Bi5O7I sample. This phenomenon further verified that the up-conversion impact of Er3+ and Yb3+ causes the improved photocatalytic efficiency of Bi5O7I sample.